Influence of MWCNTs on strength properties of high viscous epoxy adhesive and fracture behavior of adhesively bonded joints. (August 2022) - Ejaz, Hassan; Mubashar, A.; Uddin, Emad; Ali, Zaib; Arif, Nabeel
Graphical abstract: Highlights: Dispersion of Multi-Walled Carbon Nanotubes (MWCNTs) via solution mixing technique in the epoxy adhesive. A significant increase of 60% in lap shear strength of adhesive joints with the addition of MWCNTs. A significant increase of 71% in toughness behavior of adhesive reinforced with MWCNTs. A significant decrease of 23% in tensile strength of adhesive reinforced with MWCNTs. Difference in strength properties of functionalized and non-functionalized MWCNTs. Abstract: In this research, the combined effects of Multi-Walled Carbon Nanotubes (MWCNTs) addition, functionalization, and filler concentration on mechanical properties of high viscous structural adhesive and strength characteristics of adhesively bonded joints were experimentally investigated. Two configurations of lap joints: single lap joint (SLJ) and double lap strap joint (DLSJ) were manufactured with Araldite 2011 adhesive. Aluminum alloy 5083 was used as adherends in the fabrication of the lap joints. Non-functionalized, carboxylate (COOH), and amine (NH2 ) functionalized MWCNTs were added in amounts of 0.25, 0.5, 0.75, and 1 wt% in the host resin. Solution mixing technique was used for mixing of MWCNTs in the host resin. The prepared adhesive was then used to make bulk adhesive samples and lap joints. The strength properties of epoxy adhesive and lap shear joints were determined by tensile testing of the specimens. For adhesive, a maximum reduction of 54% in elastic modulus and 23% in tensile strength was observed with the addition of 1 wt% functionalized MWCNTCOOH . The decrease in strength was inversely related to failure strain, consequently increasing the toughness characteristics of the adhesive. The lap joints showed a significant improvement in joint strength with the added MWCNTs. A maximum improvement of 60% for SLJ and 31% for DLSJ was observed with the addition of 1 wt% non-functionalized MWCNTs. ANOVA study was performed for the evaluation of data variation and interaction. Optical and Scanning Electron Microscopy (SEM) was utilized for the analysis of fracture surfaces, and the correlation between nano-reinforcement and strengthening mechanisms was critically discussed.